The Commodity Cycle in Latin America : Mirages and Dilemmas - de la Torre, Augusto (Washington, DC: World Bank, 2016)
This semiannual report – produced by the Office of the Chief Economist for Latin America and the Caribbean (LAC) of the World Bank – analyzes the economic and financial performance of LAC in light of the commodity price cycle. Chapter 1 covers short-term prospects, identifies the external factors affecting the economic slowdown, and focuses on the policy challenges faced by the region (South America in particular) in terms of the monetary, fiscal, external and social adjustments required to accommodate the new external environment. Chapter 2 reviews the region’s experience during the commodity cycle, links it with the external environment, and identifies low saving as a key determinant of both the macroeconomic performance during the cycle and the constrained policy space policy makers now face, in some countries more than others. The chapter concludes with a discussion of the policy choices the region now faces, both for the immediate future and for the longer run.